A programme written by citizens? Agenda-setters and veto players in drafting the 2018 election manifesto of the Five-star Movement. Issue 3 (3rd July 2022) - Mikola, Bálint
ABSTRACT: Bottom-up policy development is integral to the concept of direct democracy and has been advertised by parties advocating this ideal as a 'revolution'. However, as election manifestos are complex documents that embrace a wide range of policy areas, such processes typically involve external advisors or party politicians specialized in a narrow policy field. Thus, the task of writing the programme is shared among several stakeholders. This raises the question of the extent to which 'citizens', i.e. party activists, can serve as agenda-setters in this process, and whether they can exclude proposals they oppose from the manifesto. The article contributes to the agenda-setting literature by exploring this puzzle through analysing the case of the 2018 election manifesto of the Five-star Movement which was 'written by citizens' and ratified in several membership ballots. A detailed analysis of the policy development process determines the distribution of agenda-setting capacities and veto powers in the construction of the M5s' election manifesto, which is contrasted with elite narratives gained from qualitative interviews with party representatives, and the findings of an online membership survey ( n = 187). The findings suggest that although party members' contribution to the agenda is negligible, some of the membership ballots granted them a substantial share of veto power. At the same time, the data indicates that few of them used this opportunity, which relegated membership ballots to a mere approval of top-down proposals. The findings challenge formalistic interpretations of direct democracy and highlight the importance of focusing on actual party practices instead.